Long-term exposure to NO2 and PM10 and all-cause and cause-specific mortality in a prospective cohort of women - Heinrich, Joachim; Thiering, Elisabeth; Rzehak, Peter; Krämer, Ursula; Hochadel, Matthias; Rauchfuss, Knut M.; Gehring, Ulrike; Wichmann, Heinz Erich (Occupational and environmental medicine, 2013)
We assessed whether long-term exposure to air pollution is associated with all-cause and cause-specific mortality during a period of declining particulate matter concentrations. - Approximately 4800 women aged 55 years from North Rhine-Westphalia, Germany, were followed for up to 18 years. Exposure to air pollution was assessed in two ways: (1) using the distance between the residential address and the nearest major road, as calculated from Geographic Information System data and (2) calculating 1-year average particulate matter concentrations below 10 µm (PM10) and nitrogen dioxide (NO2) levels using data from the nearest air-monitoring station data to the subjects’ residences. Ninety-two per cent of all subjects lived in the same community during the entire follow-up period. Associations between mortality and exposure were assessed using Cox's proportional hazards models, including confounder adjustment. - Sixteen per cent of women passed away during the follow-up period. An increase of 7 μg/m3 PM10 (IQR) was associated with an increased HR for all-cause (HR 1.15, 95% CI (1.04 to 1.27)), cardiopulmonary (HR 1.39, 95% CI (1.17 to 1.64)), and lung cancer mortality (HR 1.84, 95% CI (1.23 to 2.74)). An increase of 16 μg/m3 (IQR) NO2 exposure was associated with all-cause (HR 1.18, 95% CI (1.07 to 1.30)) and cardiopulmonary mortality (HR 1.55, 95% CI (1.30 to 1.84)). The association between cardiopulmonary mortality and PM10 was reduced for the extended follow-up period, during which PM10 concentrations (but not NO2 concentrations) were lower. Living close to a major road was associated with an increased relative risk for all-cause, cardiopulmonary and respiratory mortality. These associations were temporally stable. - Long-term exposure to ambient PM10 and NO2 was associated with increased mortality rates.
Published online first 8 December 2012
Im Titel sind die Zahlen "2" und "10" tiefgestellt
Gesehen am 15.08.2022